Enhanced Photocatalytic Degradation of Biorefractory Pollutants in Petroleum Refinery Wastewater - Abeish, Abdul Basit Mohamad S. (Curtin University, 2015)
The removal of organic pollutants from petroleum refinery effluent is a matter of great interest in the field of wastewater treatment. This research focuses on the effectiveness of solar photocatalytic degradation to degrade biorefractory pollutants present in petroleum refinery wastewater. The enhancement of solar photocatalytic degradation employed in this research was performed using different chemical enhancers such as iron oxides and hydrogen peroxide. Kinetic reaction models were successfully developed to predict the degradation rate of pollutants.